Toxicity evaluation and initial characterization of the venom of a Colombian Latrodectus sp. (January 2017) - Rueda, Alexandra; Realpe, Emilio; Uribe, Alfredo
Abstract: The genus Latrodectus has not been studied in Colombia even though it is medically important worldwide; there are three species for the country, this study focused on a non-identified species found in the Tatacoa Desert in the Huila Department. This research is the first approximation to the extraction, composition analysis and toxicity evaluation of the venom of a species of the genus Latrodectus in Colombia; and aims to evaluate the toxicity by the initial characterization of its venom. The venom extraction was accomplished with electrostimulation and total protein concentration was determined by the Lowry method and BCA assays from crude venom; with these methods, high protein concentration of the samples was measured. Bioassays on mice were also made to evaluate the toxicity and compare the symptoms produced by this Colombian spider to the Latrodectism Syndrome. Finally, an SDS-PAGE electrophoresis was used to separate the main components of high molecular weight from the samples and compared to a control of the venom of Latrodectus mactans to determine if the venom composition is different between these two species. Highlights: First analysis of venom from an undescribed Latrodectus sp. in Colombia. Symptomatology comparison between the Colombian species and the Latrodectism syndrome showed similarities in the models. The SDS-PAGE confirmed the presence of high molecular weight proteins in the crude venom that could represent toxins.